Firm Investment Decisions, Dividend Policy, And Director Stock Options - Boumosleh, Anwar (2012)
Since risk plays a role in setting dividend policy and granting stock options to directors, the paper investigates the effect of director compensation structure on the riskiness of the firm’s investment strategy by examining the firm’s dividend payout policy. The results imply that stock options to outside directors increase the firm’s appetite for risk and suggest that director stock options constitute a major incentive to changing corporate policies. The results also indicate that director stock options align the risk preferences of managers and directors. Finally, the results suggest that stock options do not motivate directors to act opportunistically in setting investment and payout policies.